Pembuatan Pakan Ikan Dengan Bahan Baku Ampas Tahu Untuk Budaya Ika Patin ( Pangisius Hypopthalmus) - Hude Dwi Venial Zega (CV. SINAR HOWUHOWU, 2026)
Feed is the primary component in the culture of striped catfish (Pangasius hypophthalmus) because it accounts for most production costs. Therefore, alternative feed ingredients that are nutritious, economical, and sustainable are needed. Fermented tofu dregs represent one promising alternative feed ingredient. This study aimed to analyze the effect of fermented tofu dregs on feed efficiency and growth performance of striped catfish based on published scientific studies. The research employed a literature review with a comparative analysis approach. Secondary data were collected from national and international scientific publications published between 2016 and 2026 through Google Scholar, Garuda, Scopus, DOAJ, and Crossref. Selected studies were screened using inclusion and exclusion criteria and analyzed descriptively by comparing growth performance, feed efficiency, Feed Conversion Ratio (FCR), Specific Growth Rate (SGR), and survival rate. The synthesis showed that fermented tofu dregs generally improved feed nutritional quality, enhanced digestibility, promoted fish growth, increased feed efficiency, reduced FCR values, and maintained high survival rates. However, their effectiveness was influenced by the type of fermentation microorganism, fermentation duration, feed formulation, substitution level, and culture conditions. Therefore, fermented tofu dregs have strong potential as an economical, environmentally friendly, and sustainable alternative feed ingredient to support striped catfish aquaculture.